Pemanfaatan Umbi Gadung Beracun (Dioscorea hispida) sebagai Bahan Baku Pembuatan Bioetanol untuk Bahan Bakar Kompor Rumah Tangga: Perancangan Distilasi Satu Tahap - Hargono Hargono (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Gadung (Dioscorea hispida) containing toxins can be utilized as a liquid fuel for household stoves or technical grade bioethanol. The technical grade bioethanol can be manufactured by using distillation tools. In this research, bioethanol was made from gadung starch). From the hydrolysis process, 7.85-10.48% glucose was produce and the fermentation process, 5-8.5 % crude ethanol. Furthermore, 1-stage distillation tools were designed to purify the crude ethanol product. Bioethanol produced from distillation tools 80%, corresponding to the technical specifications desired. Design of 1-stage distillation tools has completed, include the shape and dimensions of the tools, i.e. the main condenser, cylinder-shaped, dimensions of diameter is 32cm and height is 45cm, cylinder-shaped feeder tank/boiler, small scale volume of 5L. At distillation column, the diameter is 9cm and length is 121cm. Column is filled with ceramic or glass type packing inside. Column equipped with thermometer to measure the temperature of ethanol-water vapor